2000
DOI: 10.1038/sj.mp.4000805
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-L-carnitine physical-chemical, metabolic, and therapeutic properties: relevance for its mode of action in Alzheimer's disease and geriatric depression

Abstract: Acetyl-L-carnitine (ALCAR) contains carnitine and acetyl moieties, both of which have neurobiological properties. Carnitine is important in the ␤-oxidation of fatty acids and the acetyl moiety can be used to maintain acetyl-CoA levels. Other reported neurobiological effects of ALCAR include modulation of: (1) brain energy and phospholipid metabolism; (2) cellular macromolecules, including neurotrophic factors and neurohormones; (3) synaptic morphology; and (4) synaptic transmission of multiple neurotransmitter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
200
0
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(211 citation statements)
references
References 171 publications
(171 reference statements)
1
200
0
10
Order By: Relevance
“…It has recently been reported in mice that the acetyl group of acetylcarnitine is used mainly for synthesis of neurotransmitters such as glutamate and aspartate in the brain [5]. Thus acetylcarnitine appears to play a role in the brain which is distinct from carnitine: this notion is consistent with the observations that acetylcarnitine but not carnitine possesses therapeutic potentials in the treatment of a wide variety of neurological disorders including chronic fatigue syndrome [27], age-dependent memory loss [6,7] and Alzheimer-type dementia [8,9]. These data strongly indicate that a transporter for acetylcarnitine is present in the brain and plays an important role for brain function.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…It has recently been reported in mice that the acetyl group of acetylcarnitine is used mainly for synthesis of neurotransmitters such as glutamate and aspartate in the brain [5]. Thus acetylcarnitine appears to play a role in the brain which is distinct from carnitine: this notion is consistent with the observations that acetylcarnitine but not carnitine possesses therapeutic potentials in the treatment of a wide variety of neurological disorders including chronic fatigue syndrome [27], age-dependent memory loss [6,7] and Alzheimer-type dementia [8,9]. These data strongly indicate that a transporter for acetylcarnitine is present in the brain and plays an important role for brain function.…”
Section: Introductionsupporting
confidence: 78%
“…Not only carnitine plays an important role in transfer of long chain fatty acids from cytosol into mitochondria for β-oxidation, but also it has been recently shown that carnitine prevents injury of normal cells caused by a anti-caner drug, cisplatin [19] and inhibits hepatocarcinogenesis via protection of mitochondria [20]. Acetylcarnitine, on the other hand, has been attracting much attention because of its pharmacological effects on various neurological disorders such as age-dependent memory loss [6,7], Alzheimer-type dementia [8,9], and chronic fatigue syndrome [5]. Therefore, OCTN2 could be a therapeutic target for cancers and neurological diseases, and since cartregulin up-regulates the expression of OCTN2 as shown here, it could be an alternative therapeutic target for these diseases through enhancement of OCTN2…”
Section: Discussionmentioning
confidence: 99%
“…116 Such effects might be mediated through the maintenance of key mitochondrial functions by ALC. 97,117 In paclitaxel-induced painful neuropathy, efficacy of ALC was associated with a reduced incidence of swollen and vacuolated mitochondria in C-fiber. 118 In addition, a more direct effect might explain acute analgesic effects of ALC through upregulation of mGluR2 receptors and downstream activation of endogenous cholinergic activity.…”
Section: Acetyl-l-carnitine: Mechanism Efficacy In Animal Models Andmentioning
confidence: 99%
“…Moreover, since we recently showed that a pretreatment with acetyl-L-carnitine (ALC) was able to prevent METH-induced activation of MMP-9, preserving the actin structural arrangement in the endothelial cells (Fernandes et al, 2014), and ALC was shown to have the potential to interact with HDAC activity (Huang et al, 2012), we reasoned that ALC could also preserve the acetylation of microtubules under METH action. ALC is a natural occurring compound that was seen to be protective by different mechanisms in several neurological conditions, including BBB dysfunction (Alves et al, 2009;Haorah et al, 2011;Muneer et al, 2011;Pettegrew et al, 2000). To verify our hypothesis, we exposed the endothelial cell line bEnd.3 to increasing doses of METH and evaluated the individual and combined action of METH and ALC on a-tubulin acetylation.…”
Section: Introduction Methamphetamine (Meth) Is a Powerful Psychostimmentioning
confidence: 99%